PENERAPAN AR (AUGMENTED REALITY) UNTUK PENGENALAN POHON DENGAN METODE MARKER - Reza, Reza Noviandy; Pangaribuan, Hotma (LPPM Universitas Putera Batam, 2022)
In the use of augmented reality this can be in various ways such as making animations on the camera or forming a shape that appears from a sign or called a marker. In this case, the researchers made an augmented reality of tree species and this is used as an education about trees that is useful for people who want to use the tree for building purposes or others. This creation requires a marker so that when the camera is directed to the marker it will bring up an object from the marker and after that it will also bring up information about the tree so you can find out basically about the tree. In this application, researcher using tool for application design is Unity 3D and for tree 3D design is Blender also use Adobe Photoshop as editing the leaf of trees. The result of this application can installed on android device for support camera AR.